Community-based Tourism Policy Strategy - Ransta L Lekatompessy; Edoardus E Maturbongs; Hubertus Oja (Universitas Musamus, Merauke, Papua, 2024)
Community-based tourism policy is an approach that seeks to maximize the utilization of natural and cultural resources in an area while minimizing environmental damage. This approach aims to involve local communities as key participants in the development of tourism destinations. The research method used for this research is a literature study. The community-based tourism policy strategy serves as a solution to optimize tourism potential and empower local communities in tourism planning, management, and development. The formulation of this policy includes community capacity building, local tourism product development, community involvement in promotion and marketing, collaboration with stakeholders, and safeguarding natural and cultural resources. By implementing this strategy, it aims to build and improve community welfare, preserve natural and cultural heritage, and encourage equitable, inclusive and sustainable tourism development. The government is expected to formulate regulations and allocate adequate budgets, facilitate the formation of local tourism institutions, and increase cooperation with other stakeholders. On the other hand, for Tourism Business Actors, to always be active in building partnerships with the community, providing opportunities for community involvement, applying sustainable tourism principles, and participating in community-based tourism promotion. In addition, the community is expected to be able to increase awareness and participation, preserve local wisdom, form tourism organizations, develop skills and creativity, and play an active role in community-based tourism promotion